Pengaruh Promosi Pendidikan Terhadap Minat Peserta Didik Baru MAN 3 Banyuwangi - Mahbub Mahbub; Eva Husnia Zen (Institut Agama Islam Darussalam Blokagung, 2020)
This research is directed to 4 points, such as (1) how is education marketing pass promotion strategy in MAN 3 Banyuwangi 2018/2019 academic year? (2) how is Man 3 Banyuwnagi new student’s interes 2018/2019 academic year (3) is there some afefect an education marketing pass promotion strategy towards MAN 3 Banyuwangi new student’s interest 2018/2019 academic year? (40 How big of an effecting education marketing pass promotion staretgy towards new student’s 2018/2019 academic year?.The type of this research was descriptif quantitative with the method product moment on the data validity test and for searching data reliability using alpha formula. Arter analyzing the data wich is collected, found that (10 education marketing pass promotion strategy in Man 3 Banyuwangi 2018/2019 academic year was good (2) Man 3 Banyuwangi new student’s interest 2018/2019 academic year was strong (3) there is an affect of education marketing pass prmotion strategy towards MAN 3 Banyuwangi new student’s interest 2018/2019 academic year (40 the affect of education marketing pass promotion strategy towards new students’ interest 2018/2019 academic year of Man 3 Banyuwangi is 53,5%.